The Effect of Teacher Performance on Student Learning Outcomes in Mathematics - Rukin Rukin; Imam Hanafi; Ahmad Muflih; Agus Wicahyono (Jurnal Pemberdayaan Masyarakat, 2025)
This study examines the effect of teacher performance on student learning outcomes in mathematics using quantitative and qualitative methods. Quantitatively, linear regression analysis revealed a strong positive correlation, with a regression coefficient of 0.563, meaning each unit increase in teacher performance led to a 0.563 unit improvement in student outcomes. The coefficient of determination (R² = 0.276) indicated that 27.6% of the variance in student achievement was explained by teacher performance, while other unexamined factors affected 72.4%. A T-test supported these findings, with a significance level of 0.01 (below the 0.05 threshold) and a t-value of 2.724, exceeding the critical value of 2.005, confirming statistical significance. These results affirm that teacher performance significantly impacts students' mathematical achievement. However, the relatively low R² suggests that other variables—such as curriculum quality, student motivation, parental involvement, or classroom environment—play essential roles. Qualitatively, the study underscores the need for further research to explore broader determinants of educational success and strategies to enhance teacher performance. By integrating both methods, the study provides a comprehensive understanding of how teacher quality shapes student learning and highlights the complexity of educational outcomes that extend beyond teacher-related factors.